A Quasi-Experimental Study on the Effect of Google Classroom-Based Blended Learning on Students’ Interest in Mathematics - Yahya, Amran; Mulbar, Usman (Universitas Sulawesi Barat, 2026)
This study aims to analyze the effect of a Google Classroom-based blended learning model on students’ interest in learning mathematics. Although previous studies have highlighted the potential of technology integration to enhance student engagement, there is still a lack of empirical research specifically examining its effect on mathematics learning interest using a quasi-experimental design in the context of Indonesian secondary education. Therefore, this study provides important contextualized empirical evidence. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of two classes of eleventh-grade students at MAN 1 Polewali Mandar, selected through purposive sampling, with a total of 60 students assigned to experimental and control groups. Data were collected using a validated mathematics learning interest questionnaire and analyzed through normality, homogeneity, and independent sample t-tests at a 5% significance level. The results showed that the mean score of students’ learning interest in the experimental class (84.33) was higher than that of the control class (72.67), with t_count=4.567 > t_table=2.000 (p<0.05). These findings indicate that Google Classroom-based blended learning has a significant effect on improving students’ interest in learning mathematics. The implication of this study suggests that integrating face-to-face and digital learning environments can create more flexible, interactive, and meaningful learning experiences, making it a promising instructional strategy for mathematics teachers in the digital era.